Survey on the surfaces generated by generalized analytic functions - Aleksandr Beknazaryan; Suren Grigoryan (National Academy of Sciences of Armenia)
In this paper some fundamental results from the theory of generalized analytic functions are presented. Then, based on that theory, we develop the theory of the so-called Bohr-Riemann surfaces.
Keywords: Mathematics; Algebraic geometry; Functions of a complex variable; Abstract harmonic analysis